## Saturday, May 14, 2022

### The Sum and Product of Roots of a Quadratic Equation

The Sum and Product of Roots of a Quadratic Equation

Introduction

Let s, t be the roots of the equation a*x^2 + b*x + c = 0.

Let:

s = (-b + √(b^2 - 4*a*c)) / (2 * a)

t = (-b - √(b^2 - 4*a*c)) / (2 * a)

Then

s + t = -b / a

s * t = c / a

We see this topic a lot in algebra, let's see how these properties are derived. Fairly simple.

Sum of the Roots

s + t

=  (-b + √(b^2 - 4*a*c)) / (2 * a) + (-b - √(b^2 - 4*a*c)) / (2 * a)

= (-2 * b) / (2 * a)

= -b / a

Product of the Roots

s * t

=  (-b + √(b^2 - 4*a*c)) / (2 * a) * (-b - √(b^2 - 4*a*c)) / (2 * a)

= (b^2 + b * √(b^2 - 4*a*c) - b * √(b^2 - 4*a*c) - (b^2 - 4*a*c)) / (4*a^2)

= (b^2 - b^2 + 4*a*c) / (4*a^2)

= (4*a*c) / (4*a^2)

Eddie

All original content copyright, © 2011-2022.  Edward Shore.   Unauthorized use and/or unauthorized distribution for commercial purposes without express and written permission from the author is strictly prohibited.  This blog entry may be distributed for noncommercial purposes, provided that full credit is given to the author.